Bagaimana Efikasi Diri Dan Dukungan Sosial Keluarga Memprediktori Motivasi Berprestasi: Sebuah Studi Kausal-Komparatif - Sumanjaya, Kadek Danang Valentino; Susilawati, Luh Kadek Pande Ary (Jurnal Ilmiah Wahana Pendidikan, 2024)
For twelfth-grade students in public high schools (SMA Negeri), the shifts in teaching methods following the COVID-19 pandemic present significant obstacles that are frequently difficult to overcome. Pupils at this level need a strong internal incentive to go through the challenges of the learning process and fulfill their goals; this motivation is often called achievement motivation. After the COVID-19 pandemic, a number of internal and external factors affect twelfth-grade students at public high schools' drive for accomplishment. Self-efficacy is an example of an internal component, and family social support is an example of an external element.This study aims to determine how self-efficacy and family social support influence the success motivation of public high school twelfth graders in Denpasar during the COVID-19 pandemic. With 206 twelfth-grade students from public high schools in Denpasar, the study used a multi-stage cluster sampling procedure with a quantitative approach.The results show that accomplishment motivation is jointly influenced by self-efficacy and family social support by 61.4% (R Square = 0.614; significance value 0.000 < 0.05). Therefore, building good family social support and encouraging self-efficacy—the belief in one's own abilities are essential to raising kids' drive for achievement.